2(x-1)^5=-64
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
5 + ( x + 27 ) = 64
( x + 27 ) = 64 - 5 ( x + 27 ) = 59 x = 59 - 27 x = 32a) \(\Rightarrow x+27=59\Rightarrow x=32\)
b) \(\Rightarrow x-2=39\Rightarrow x=41\)
c) \(\Rightarrow x+5=-322\Rightarrow x=-327\)
d) \(\Rightarrow5x=35\Rightarrow x=7\)
e) \(\Rightarrow4\left(x-5\right)=56\Rightarrow x-5=14\Rightarrow x=19\)
f) \(\Rightarrow15+x=37\Rightarrow x=22\)
g) \(\Rightarrow7\left(13-x\right)=35\Rightarrow13-x=5\Rightarrow x=8\)
h) \(\Rightarrow10\left(x+1\right)=100\Rightarrow x+1=10\Rightarrow x=9\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(1,\Rightarrow4^{x+1}=4^{3x}\\ \Rightarrow x+1=3x\\ \Rightarrow2x=1\\ \Rightarrow x=\dfrac{1}{2}\\ 2,\Rightarrow5x-2x=10+10x\\ \Rightarrow7x=-10\\ \Rightarrow x=-\dfrac{10}{7}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
(-3/4)63x-1=(3/4)^3
3x-1=3+1
3x=3=1
x=4;3
x=4/3
Vậy x=4/3
![](https://rs.olm.vn/images/avt/0.png?1311)
53 + (124 - x) = 87
(124 - x) = 87 - 53
(124 - x) = 34
x = 124 - 34
x = 90
12.x - 64 = 25
12.x - 64 = 32
12.x = 32 + 64
12.x = 96
x = 96 : 12
x = 8
![](https://rs.olm.vn/images/avt/0.png?1311)
a: =>2x=-18+5=-13
=>x=-13/2
b: =>3^x-1=81
=>x-1=4
=>x=5
c: =>4(5-x)=24
=>5-x=6
=>x=-1
![](https://rs.olm.vn/images/avt/0.png?1311)
1.
a) \(2^x=128\)
\(2^x=2^7\)
\(=>x=7\)
b) \(8^{x-1}=64\)
\(8^{x-1}=8^2\)
\(=>x-1=2\)
\(x=2+1\)
\(=>x=3\)
c) \(3+3^x=30\)
\(3^x=30-3\)
\(3^x=27=3^3\)
\(=>x=3\)
d) \(\left(x+2\right)=64\) -> đề có thiếu không vậy?
e) \(3^2.x=3^5\)
\(x=3^5:3^2\)
\(=>x=3^3=27\)
f) \(\left(2x-1\right)^3=343\)
\(\left(2x-1\right)^3=7^3\)
\(=>2x-1=7\)
\(2x=7+1\)
\(2x=8\)
\(x=8:2\)
\(=>x=4\)
\(#Wendy.Dang\)
a,\(2^x\)=128 b,\(8^{x-1}\)=64 c,3+\(3^x\)=30 d,x+2=64
\(2^7\)=128 \(8^{x-1}\)=\(8^2\) \(3^x\)=30-3 x=64-2
=>x=7 =>x-1=2 \(3^x\)=27 x=62
x=2+1=3 \(3^x\)=\(3^3\)
=>x=3
e,\(3^2\).x=\(3^5\) f,(2x-\(1^3\))=343
x=\(3^5\):\(3^2\) 2x=1+343
x=27 2x=344
x=344:2
x=172
![](https://rs.olm.vn/images/avt/0.png?1311)
\(5\left(x-1\right)+3=43\)
\(5\left(x-1\right)=40\)
\(x-1=8\)
\(x=9\)
\(\left(1+2+3+...+50\right)+x=5050\)
\(\dfrac{50\left(50+1\right)}{2}+x=5050\)
\(1275+x=5050\)
\(x=3775\)
\(\left(2x+1\right)^3=64\)
\(\left(2x+1\right)^3=4^3\)
\(2x+1=4\)
\(2x=3\)
\(x=1,5\)
\(2\left(x-1\right)^5=-64\)
=> \(\left(x-1\right)^5=-64:2=-32\)
=> \(\left(x-1\right)^5=\left(-2\right)^5\)
=> x - 1 = -2
=> x = -1